Results of community-based TB and HIV screening among transgender women and male sex workers in Pakistan. - Sharaf Ali Shah; Shahina Qayyum; Saifullah Baig; Nikhat Iftikhar; Rubab Lubna Bukhari; Wajid Ali; Marina Smelyanskaya; Jacob Creswell (Public Library of Science (PLoS), 2023)
In Pakistan and globally, a large proportion of people with TB who are not receiving treatment are key populations with poor access to diagnosis and care. Transgender women and male sex workers (MSW) are heavily stigmatized and marginalized groups. While HIV rates are well documented among these key populations, little such data exists for TB. We engaged local organizations working with transgender women and MSW communities in Karachi and five urban cities in Sindh Province. People from the communities served as screening facilitators and treatment supporters. Verbal screening was followed by testing with Xpert MTB/RIF and HIV testing was offered. People with TB were supported through treatment. We screened 18,272 transgender women and 24,253 MSW. 8,921 (21.0%) individuals had presumptive TB and 7,472 (83.8%) provided sputum samples. We detected 438 (5.9%) people with positive results including 140 transgender women and 298 MSW. Including people diagnosed clinically, 625 people with TB were identified and 98.1% initiated treatment. Overall, 1.5% of people screened had TB, 1.7% among MSW and 1.1% among transgender women. Of 1,508 people tested for HIV, 243 had HIV infection (HIV+). The rates of TB among HIV+ transgender women (8.8%) were slightly lower than among MSW (10.3%). Previously, few attempts have been made to address TB in transgender women and MSW. Our work shows that these groups carry a significant burden of both TB and HIV in Pakistan and do not regularly access services. Effective interventions should include the engagement of community leaders and peers.